1997
DOI: 10.1093/emboj/16.12.3544
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of murine melanocyte function invitro by agouti signal protein

Abstract: Molecular and biochemical mechanisms that switch melanocytes between the production of eumelanin or pheomelanin involve the opposing action of two intercellular signaling molecules, α‐melanocyte‐stimulating hormone (MSH) and agouti signal protein (ASP). In this study, we have characterized the physiological effects of ASP on eumelanogenic melanocytes in culture. Following exposure of black melan‐a murine melanocytes to purified recombinant ASP in vitro, pigmentation was markedly inhibited and the production of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
95
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 38 publications
9
95
1
Order By: Relevance
“…In vivo, ␣MSH promotes the production of eumelanin, while expression of the agouti gene promotes the production of pheomelanin. In vitro studies have shown that ASP could induce pheomelanogenesis in eumelanic melanocytes (30,33) demonstrating that ASP alone is sufficient to elicit such changes. It has also been shown that ASP could down-regulate the stimulation of melanogenesis induced by forskolin and ␣MSH (30,31).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In vivo, ␣MSH promotes the production of eumelanin, while expression of the agouti gene promotes the production of pheomelanin. In vitro studies have shown that ASP could induce pheomelanogenesis in eumelanic melanocytes (30,33) demonstrating that ASP alone is sufficient to elicit such changes. It has also been shown that ASP could down-regulate the stimulation of melanogenesis induced by forskolin and ␣MSH (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that ASP could induce pheomelanogenesis in eumelanic melanocytes (30,33) demonstrating that ASP alone is sufficient to elicit such changes. It has also been shown that ASP could down-regulate the stimulation of melanogenesis induced by forskolin and ␣MSH (30,31). In this report, we show that ASP can by itself inhibit spontaneous and induced-differentiation of melanoblasts into melanocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To further test the role of protein trafficking and eumelanosome formation in influencing melanoma drug sensitivity, we used an alternative method to moderate both processes. The binding of the melanocyte-stimulating hormone (MSH) to the MC1R on the cell surface of melanocytes has been shown to increase mature eumelanosome number, whereas binding of the antagonist agouti-signaling peptide (ASIP) to the receptor causes a decrease in mature eumelanosome formation (16)(17)(18). MSH binding to the MC1R has also been shown to influence the trafficking of the catalase protein (19).…”
Section: Chemosensitivity Is Up-regulated or Down-regulated By Receptmentioning
confidence: 99%